Early detection of SARS‐CoV‐2 and other infections in solid organ transplant recipients and household members using wearable devices. (5th May 2021) - Keating, Brendan J.; Mukhtar, Eyas H.; Elftmann, Eric D.; Eweje, Feyisope R.; Gao, Hui; Ibrahim, Lina I.; Kathawate, Ranganath G.; Lee, Alexander C.; Li, Eric H.; Moore, Krista A.; Nair, Nikhil; Chaluvadi, Venkata; et al.
Summary: The increasing global prevalence of SARS‐CoV‐2 and the resulting COVID‐19 disease pandemic pose significant concerns for clinical management of solid organ transplant recipients (SOTR). Wearable devices that can measure physiologic changes in biometrics including heart rate, heart rate variability, body temperature, respiratory, activity (such as steps taken per day) and sleep patterns, and blood oxygen saturation show utility for the early detection of infection before clinical presentation of symptoms. Recent algorithms developed using preliminary wearable datasets show that SARS‐CoV‐2 is detectable before clinical symptoms in >80% of adults. Early detection of SARS‐CoV‐2, influenza, and other pathogens in SOTR, and their household members, could facilitate early interventions such as self‐isolation and early clinical management of relevant infection(s). Ongoing studies testing the utility of wearable devices such as smartwatches for early detection of SARS‐CoV‐2 and other infections in the general population are reviewed here, along with the practical challenges to implementing these processes at scale in pediatric and adult SOTR, and their household members. The resources and logistics, including transplant‐specific analyses pipelines to account for confounders such as polypharmacy and comorbidities, required in studies of pediatric and adult SOTR for the robust early detection of SARS‐CoV‐2, and other infections are also reviewed.